(3SjGSGJ JbGSe Gdbhi (B:s (3GdchfZQS h GdSdWI GdJfajPjI (B/s - (3MeGO, eGRf ajTQdhjSs ((3YeGf (B:s (3CdCgdjI ddfTQ h GdJhRjY ,s, 1994)
(3jWQM gPG GdcJGH SDGdG eQcRjG (B: (3cja deHOC aUd GdSdWGJ Gf jYed CKfGA GdJWHjb? h jKjQ gPG GdSDGd YOOG ef GdbVGjG (B. (3aEdi Cj MO jTGQc GdQFjS ceTQhY ? h HCj bOQ jJONd GdchfZQS aj GdeSGFd GdEOGQjI? h eGgj GdeTGcd GdSjGSjI GdOSJhQjI dgPG GdJbGSe ddSdWI? Gf GdaUhd GdeSJbdI Mhd GdHjQhbQGWjI h GddLGf GdJfXjejI GdeSJbdI JOQS gPg GdeSGFd HYeb CcHQ h ef RhGjG eNJdaI h jYGdL aUd LOjO CVja Gdi gPg GdWHYI SdWGJ GdMQH h GdSjGSI GdNGQLjI GdfRGYGJ GdJfajPjI (B- (3GdJTQjYjI GdJj JDKQ Ydi GdYdGbGJ GdYGdejI HeG aj Pdc bVjI GjQGf (B- (3chfJQG(B- (3h MQH GdNdjL dYGe (B1991.s
Keywords: (3SdWI JfajPjIs; (3hdGjGJ eJMOI GeQjcjIs